The Variability for the Biochemical Indicators at the Winter Wheat Assortment and Identifying the Sources with a High Antioxidant Activity - Ramona Aida Paunescu; Elena Bonciu; Elena Rosculete; Gabriela Paunescu; Catalin Aurelian Rosculete; Cristina Babeanu (Plants, 2021)
This study presents the variability of some biochemical indicators in the winter wheat assortments tested in south-western Oltenia (Romania) and identification of the sources showing a high antioxidant activity. The peroxidase activity has intensified as the stress induced by treatment with PEG of different concentrations and in different doses increased. Regarding the peroxidase content, among the varieties treated with PEG 10,000 25%, the majority of the Romanian varieties tested showed higher values of the PEG/control treatment ratio, which suggests tolerance to drought. In reverse, the activity of ascorbate peroxidase is lower in tolerant varieties. The varieties with a subunit report have been noted. Among them are the Izvor variety, known as the drought-tolerant variety, as well as other Romanian varieties: Alex, Delabrad, Lovrin 34, etc. An increased activity of catalase was present in most varieties, so there is the possibility of drought tolerance. Among the varieties highlighted are Romanian varieties (Dropia, Trivale, Nikifor, etc.) but also foreign varieties (Kristina, GH Hattyu, Karlygash, etc.). However, the correlation between yield index in the limited assortment and the antioxidant enzyme content ratios between PEG and control treatments does not exist, suggesting that none of these biochemical indicators are a selective indicator for drought tolerance under the experimental condition.